The Castrated Phallic God: Representations of Kurupi in Brazilian Religious Education - Stern, Fábio L. (International journal of Latin American religions, 2025)
Kurupi, a phallic Tupi-Guarani deity widely worshipped across Latin America, takes on distinct cultural adaptations in Brazil, influenced by significant historical forces. Despite the impact of the Tupi language on Brazilian culture, the colonial-era criminalization of Indigenous practices and later adaptations have resulted in a desexualized portrayal of Kurupi in Brazilian classrooms. This study compares representations of Kurupi by religious education teachers from São Paulo and the Amazon region. While educators in the Amazon tend to lean towards traditional Indigenous portrayals, teachers in São Paulo often incorporate syncretic elements, blending Indigenous and African influences shaped by popular media. We explore how these portrayals reflect broader trends in Orientalism and show how the Brazilian education system reshapes Indigenous myths to align with dominant urban perspectives, separating them from their cultural roots.